Tax and spending in 2024-2025 - Bee Boileau; David Phillips; Tom Waters; Tom Wernham (Institute for Fiscal Studies (IFS), 2024)
This chapter of our second annual Budget Report looks at Scottish tax policy and revenue, the overall amount of funding available for Scottish public services, and planned spending on different individual services in the coming financial year, 2024-25. In several important respects, the Scottish Government's 2024-25 Budget represents a continuation of trends seen in recent years. On the tax side, as with the current year, increases to income tax on those on higher incomes are set to raise a modest amount, but much more important have been significant upwards revisions to forecast underlying tax revenues. Combined with (more modest) increases in block grant funding from the UK government, this means that in cash terms, funding for public services in the coming year will be 1.7 billion higher than expected this time last year, and fully 2.6 billion more than expected in the May 2022 Scottish Resource Spending Review. Notwithstanding the recent sharp drop, inflation has still proved higher and more stubborn than expected back in May 2022. This almost fully offsets the boost to cash budgets. In addition, the boosts to spending that have been much highlighted by the Scottish Government again overstate the increase in resources available for public services next year - by ignoring top-ups made to the current year's budgets since the Budget Bill was initially passed.
Keywords: 330; Government finances and spending; Health and social care; Taxes and benefits; Scottish Budget 2024-25; Devolved government finances; Distributional effects; Government spending; Healthcare; Income taxes; Local government finance; Property taxes; Public finance; Public sector; Tax